Magnetic properties of Yamato-791197 in comparison with those of lunar highland anorthositic breccias - Nagata, Takesi; Funaki, Minoru (1986)
P(論文) Magnetic properties of Yamato-791197 anorthositic breccia meteorite are compared with those of lunar highland anorthositic breccias and rocks such as Apollo 15418,66055,68815,60016 and others. Thermomagnetic curve characteristics of Y-791197 and all lunar anorthositic breccias and rocks show the coexistence of almost pure metallic iron and kamacite of about 5% Ni, associated with a small amount of taenite. The coexistence of almost pure metallic iron, which are primary lunar components and/or a product of the breakdown of Fe-bearing minerals such as fayalite caused by impact metamorphism, together with kamacite is very common in lunar surface materials. The coexistence of iron and kamacite has never been observed in achondrites and other stony meteorites. It is therefore highly plausible that Y-791197 is a fragment of lunar highland anorthositic material, which was explosively ejected from the lunar surface. The specific paramagnetic susceptibility (χ_P) of Y-791197 (χ_P=(0.85-1.2)×(10)^<-5>emu/g/Oe at 300K) is much smaller than that of ordinary achondrites, but very common for lunar anorthositic rocks and breccias. Ferromagnetic hysteresis behavior of Y-791197 has typical characteristics of lunar surface materials, which indicate the coexistence of superparamagnetically fine metallic iron particles. The NRM characteristics of Y-791197 also are in harmony with those of lunar highland anorthositic breccias and rocks. departmental bulletin paper